DETERMINATION OF INTERNET RIGHTS IN LAW COUNTRY: JURISDICTIONAL ACTIONS OF GOVERNMENT VIOLATIONS AGAINST THE LAW AND PRINCIPLES OF HUMAN RIGHTS IN INDONESIA - Merdian Lisa (Ensiklopedia Research and Community Service Review, 2026)
Abstract: This study aims to explain the legal reasons behind the narrative of the judgments taken by judges regarding the justification for limiting internet access rights as the construction of articles on content restrictions involving violations of the law in the ITE Law is contrary to human rights principles and describe how the application of human rights principles used in decisions as a metawacana that underlies judges to adopt these human rights principles, both constitutionally and based on derivative laws and regulations. This study examines decision number 230/G/TF/2019/PTUN-JKT. This study is a normative-philosophical legal research through a statutory, conceptual, and case study approach. The author concludes that every Indonesian citizen has a good reason to get and enjoy Internet access as a human right. Internet access is not only a luxury for those who can afford it, but also necessary for individuals to live a minimally decent life especially in area far from the State Capital such as Papua and West Papua. Therefore, the restriction and/or slowdown of internet access (throttling/blocking) carried out by the government through press releases from the ministry of communication and information in the Papua and West Papua regions as a preventive effort to prevent the spread of fake, provocative, hoax, and hate speech is an act against state/government law because (1) the product of limiting human rights to access the internet (internet rights) through throttling/blocking can only be carried out based on the law and the principle of proportionality (2) the government's authority is only limited to terminating access to electronic information and/or electronic documents that have unlawful content and do not include severing internet network access, (3) the government's actions substantially contradict the requirements of human rights restrictions. The application of universal human rights principles is accommodated in the decision as stipulated in Article 28 J paragraph (2) of the 1945 Constitution, Article 73 of the Human Rights Law, Article 19 paragraph (3) of the ICCPR. Keywords: Internet Rights, Human Rights, Decisions, And Law Country.